Optimalisasi Pemasaran Strategik Melalui Employee Benefit Program :Studi Kasus Bank Muamalat Kcp Batu Di Pesantren - Masalingi, Abdurrahman; Haryanti, Peni (At-Tauzi : Jurnal Ekonomi Islam, 2024)
Abstract: Optimization of Strategic Marketing Through Employee Benefit Programs: A Case Study of Bank Muamalat KCP Batu in Pesantren. This study aims to explore the application of the Employee Benefit Program (EBP) as a marketing strategy at Bank Muamalat KCP Batu, focusing on Islamic boarding schools (pesantren). A case study approach was used to analyze how EBP can strengthen the synergy between the bank and pesantren, enhance customer loyalty, and expand market penetration. The researcher conducted participatory observations during the internship and in depth interviews with Bank Muamalat management and pesantren administrators. The results indicate that EBP has a significant positive impact on customer engagement and loyalty in pesantren. However, the study also identified challenges, such as low financial literacy and limited technological infrastructure in pesantren. Thus, a more segmented and adaptive marketing approach is necessary to address these obstacles. In conclusion, EBP proves to be an effective strategy in increasing financial inclusion within pesantren communities and strengthening the bank’s relationship with religious institutions in Indonesia..